Effect of Intravitreal Anti-Endothelial Growth Factor Agents on Renal Function in Patients With Diabetes Mellitus - Marta Rivero; María Fernández-Vidal; Justo Sandino; Raquel Berzal Rico; Candela Moliz; José Enrique Ruiz-Cabello; Lucía Cordero Garcia-Galán; Celia González-García; Paúl Hernández-Velasco; Julián Segura; Eduardo Gutiérrez; Enrique Morales (Kidney International Reports)
Introduction: Intravitreal administration of vascular endothelial growth factor inhibitors (anti-VEGF) is the treatment of choice in retinal pathology associated with type 2 diabetes mellitus (DM2). We aimed to analyze the effect of intravitreal anti-VEGF administration on renal function in patients with DM2. Methods: This is a single-center retrospective and observational study of patients with DM2 with and without chronic kidney disease (CKD). We analyzed the evolution of renal function after anti-VEGF onset, compared with a control group. Results: We included 45 patients (55.6% male) who received anti-VEGF therapy. Mean age was 74.4±11.5 (50–91) years. These were compared with 45 patients with similar characteristics. After 12 months, 76.3% had CKD with a mean reduction in estimated glomerular filtration rate (eGFR) of 19.4%. Nine patients (20%) had a >25% reduction in eGFR, and 3 patients (6.7%) had a >50% reduction in GFR. At 24 months, 80% of patients had CKD with a mean eGFR decrease of 28%. The mean eGFR slope of patients who had received anti-VEGF treatment was 10 ml/min/year compared to 1.5 ml/min/year in the control group (P < 0.05). After the first administration, 5 patients (17.2%) in the CKD group required renal replacement therapy during follow-up (mean time 22±12 months). Main risk factors for need of dialysis were age, presence of previous CKD, and baseline proteinuria. Conclusion: Intravitreal anti-VEGF administration is a risk factor for CKD and rapid progression to end-stage kidney disease in patients with previous CKD. Knowing these drugs' implications is crucial to avoid CKD progression and opportunely limit their use in certain patients.